Cost of your guitar = $ 600
Let your friend's guitar's cost be = n
According to the question =
Your guitar costs $ 40 more than twice the cost of your friend's guitar which is n ,but your guitar's cost is $ 600.
So ,the linear equation for this will be =
= 2n+$40 = $600
= 2n = $600-$40
= 2n = $ 560
= n = $ 560/2
= n = $ 280
Thus ,the cost of your friend's guitar is $ 280.The cost of your friend's guitar is $280 by creating an equation based on the cost comparison to your own guitar, and then solving for the variable representing your friend's guitar's cost.
You paid $600 for a new guitar, which costs $40 more than twice the cost of your friend's guitar. To find the cost of your friend's guitar, let's denote the cost of your friend's guitar as x. According to the information given, your guitar's cost can be represented by the equation 2x + $40 = $600. Solving for x will give us the following steps:
Subtract $40 from both sides of the equation: 2x = $600 - $40.
This simplifies to 2x = $560.
Divide both sides by 2: x = $560 / 2.
Therefore, x equals $280.
The cost of your friend's guitar is $280.
Turner mesuares 3/4 foot of a ribbon for a coustume. He needs 9 pieces of ribbon with the same length
Answer:
6¾
Step-by-step explanation:
¾ * 9/1 = 287/4
27/4=6 ¾
which equals 6.75
A plane takes off from City A and goes towards city B at noon. After arriving in city B it has a 5 hour layover before returning. During the return flight the plane runs into a headwind that causes it to go 20 mph slower than the original flight and makes the flight back one more take one extra hour more than the original time. Write an equation that represents the total time traveled with clearly labeled variables
5y² + 2xy – 20x - 100
Step-by-step explanation:
Assume that the distance between City A and City B is x miles,
& the speed of the plane from City A to B is y mph;
The return trip is 20 mph slower so the plane's speed is (y – 20) mph
Since time = distance/speed; The time taken by the plane from City A to B is x / y hrs.
The time taken in return flight is;
x / (y - 20) hrs
The layover was 5hrs long. Therefore the total time taken on the who return trip journey is;
x/y + x/(y-20) + 5
multiply each individual fraction with the LCM of the denominators
x(y-20) + xy + 5 y(y-20)
xy -20x +xy + 5y² – 100
5y² + 2xy – 20x - 100
Felix's parents opened a savings
account for him when he was born with
a $2,000 deposit. The account earns 6%
compound interest, compounded
annually. How much money will be in
Felix's account when he is 21?
The money in the Felix's account will be $6798 when he is 21.
Step-by-step explanation:
It is given that,
The amount deposited is $2000.The account earns 6% compound interest.It is compounded annually for 21 years.To find the money in Felix's account after 21 years :
The formula used here is,
⇒ [tex]A = P(1+r/n)^{nt}[/tex]
where A is the amount after 21 years.
P is the initial amount deposited ⇒ P = 2000r is the rate ⇒ r = 0.06n is the number of times interest is compounded per year⇒ n = 1 t is the time period ⇒ t = 21⇒ [tex]2000(1+0.06/1)^{21\times 1}[/tex]
⇒ [tex]2000(1.06)^{21}[/tex]
⇒ [tex]2000\times3.399[/tex]
⇒ [tex]6798[/tex]
Therefore, The money in the Felix's account will be $6798 when he is 21.
A pool is in the shape of a rectangular prism. On Monday, water was pumped out of the pool at a constant rate, starting at 12:00pm. At 12:15 pm, the water in the pool was 45 inches deep. At 12:35 pm, the water in the pool was 41 inches deep.
Part A
How many inches does the depth of the water decrease each minute?
Part B
Write an equation that represents y, the depth of the water (in inches) after x minutes.
Answer:
the equation is y = (-2/15 in/min)x + 43 in
Step-by-step explanation:
We'll represent elapsed time with the letter t. Then 12 p.m. corresponds to t = 0 sec. Between 12 p.m. and 12:15 p.m., the change in time was 15 min and the change in water depth was (45 - 41) in., or 4 in.
Thus, the water depth changes by 4 in (a decrease) over 30 min.
Part A: The water depth rate of change is -4 in/30 min, or -2 in/15 min, or
(-2/15 in)/min (the depth is decreasing).
Part B: We need to derive a linear function that describes the water depth at any given time x (or t). Two points on the graph of this line are
(15 min, 45 in) and (35 min, 41 in): the 'run' is 30 min and the 'rise' is -4 in.
As in Part A, the slope of this line is (-2/15 in)/min.
The desired equation is then y = mx + b, or 45 in = (-2 in/15 min)(15 min) + b, or 45 in = 2 in + b, or 43 in = b. Then, in its most general form,
the equation is y = (-2/15 in/min)x + 43 in
The exponential function g(x) is shown on the graph. Suppose f(x) = x. Which statement is true when comparing the domain of f(x) to the domain of g(x)?
A) The domain for both functions is all positive numbers.
B) The domain for both functions is all integers.
C) The domain for both functions is all real numbers.
D) The domain for both functions is all real numbers greater than 0.
Answer: The domain for real numbers
Step-by-step explanation: taking it right now
The domain for both functions g(x) and f(x) is all real numbers. Then the correct option is C.
What is a domain?The domain means all the possible values of the x.
The exponential function g(x) is shown on the graph.
Suppose f(x) = x.
Then the domain of the function g(x) is a real number.
And the domain of the function f(x) is also a real number.
Then the domain for both functions is all real numbers.
More about the domain link is given below.
https://brainly.com/question/12208715
What is the positive negative square roots of 64?
The answer explains the positive and negative square roots of 64.
When dealing with the square roots of a number like 64, remember that the square root of 64 is 8, both positive and negative. This is because (-8) x (-8) equals 64 just like (8) x (8) equals 64, following the rule that multiplying two negative numbers results in a positive number.
i really need help :( i dont get help from anyone :(
Answer:
D.) 12x -6x 90
Step-by-step explanation:
because it's right angle
what is the solution to x^2 = 121?
Answer: {11, -11}
Step-by-step-explanation: To solve for x in this equation, since x is squared, we simply take the square root of both sides of the equation to get x by itself.
It's important to remember however that when taking the square root of both sides of an equation, we always use plus or minus.
In other words in this problem, since x² = 121,
x = + or - 11.
A common mistake is to say that x is just equal to 11. But notice that if you plug a -11 back into the original equation, it also checks.
So our answer to this problem is {11, -11}.
Answer: either 11 or -11
Step-by-step explanation:
you have to square root both sides. Then, you are left with the equation [tex]\sqrt{x^{2} } = \sqrt{121}[/tex]. That means that x either equals to 11 or -11.
:)
(9+q)(8-q)= polynomial in standard form
Answer:
- q² - q + 72
Step-by-step explanation:
To express the given expression as a polynomial in standard form, we would first multiply the individual elements in one parenthesis with the elements in the second.
We would then rearrange the outcome and simplify it algebraically.
The arrange it in the order of the unknown variable.
As such,
(9+q)(8-q) = 9(8-q) +q(8-q)
= 72 -9q + 8q - q²
= 72 - q - q²
= - q² - q + 72
To form the expression (9+q)(8-q) into a polynomial in standard form, we multiply the terms using the distributive property to get -q² - q + 72.
The student has asked for the expansion of a binomial expression into polynomial form, in this case, expanding (9+q)(8-q). The process involves using the distributive property, also known as the FOIL method (First, Outer, Inner, Last), to multiply each term in the first binomial by each term in the second.
Expanding the binomials, we have:
First: 9 × 8 = 72
Outer: 9 × (-q) = -9q
Inner: q × 8 = 8q
Last: q × (-q) = -q²
Combining like terms (-9q and 8q) gives -q and then adding to the remaining terms, we have:
72 - q - q²
Reordering to get the polynomial in standard form (highest degree first), the result is:
-q² - q + 72
Whitch fraction is equivalent to 5/20
Answer:
1/4
Step-by-step explanation:
5/20
Divide the top and bottom by5
1/4
I need help:
The width of this rectangle is 1/3 of the length. Find the length and the width of the rectangle.
Answer:
3(y-4) =2y+6
3y - 12 = 2y +6
y = 18
so length is 42 in.
width is 14 in.
After solving the given equations, the length of the rectangle is 42 inches and the width of the rectangle is 14 inches.
What is an equation?Equations are mathematical expressions that have two algebra on either side of an equal (=) sign. The expressions on the left and right are shown to be equal to one another, demonstrating this relationship. L.H.S. = R.H.S. (left-hand side = right side) is a fundamental simple equation.
The given data in the question,
According to the given diagram,
Length of the rectangle, L = 2y + 6 inches (i)
Width of the rectangle, W = y - 4 inches (ii)
The width of the rectangle is 1/3 of the length,
1/3(2y + 6) = (y - 4)
2y + 6 = 3y - 12
y = 18.
Substitute y = 18 in equation (i)
L = 2(18) + 6
L = 42 inches
Substitute y = 18 in equation (ii)
W = (18 - 4)
W = 14 inches.
To know more about equation:
https://brainly.com/question/10413253
#SPJ2
The supply and demand curves for a product line of bicycles are shown. Approximately where is the equilibrium point?
Answer:
The answer is B (132,220)
Step-by-step explanation:
I got it correct on the test
Plato tests
The required equilibrium point for the supply and demand curves for a product line of bicycles is (135, 225).
What is the graph?The graph is a demonstration of curves that gives the relationship between the x and y-axis.
here,
The graph shows the supply and demand curves for a product line of bicycles.
To determine the equilibrium point we to locate the intersection point of supply and demand.
From the graph, the intersection point is (135, 225), which is the approximate equilibrium point.
Thus, the required equilibrium point for the supply and demand curves for a product line of bicycles is (135, 225).
Learn more about graphs here:
brainly.com/question/16608196
#SPJ5
if a circle has a radius of 2 ft. is the circumfrence and area the same? Explain
Answer:no
Step-by-step explanation:
The circumference and radius are different
The circumference and the area of the circle is same.
Step-by-step explanation:
Given,
The radius (r) of the circle = 2 ft
To find the circumference and the area of the circle.
Formula
The circumference of a circle = 2πr
The area of a circle = πr²
Now,
The circumference of a circle = 2π×2 = 4π
The area of a circle = πr² = π×2² = 4π
Hence,
The circumference and the area of the circle is same.
What number must you add to complete the square?
x^2+12x=5
Answer:
36
Step-by-step explanation:
12/2 = 6
6^2 = 36
what is the "X" in x2 − 70 = –69 plz need asap
Answer:
1,-1
Step-by-step explanation:
Answer:
X = 1/2
Step-by-step explanation:
x2 = -69 + 70
x2 = 1
x = 1/2
I’m lost and unsure what is the first step to do find width of da roof
Answer:
You set up an equation, using the trig function "tan" to find half of the roof (the equation would be tan(24) = 3.5/x, where x = 1/2 roof width)
Step-by-step explanation:
That would be the first step.
You solve the equation for x, and then multiply x by 2 to get the width of the roof.
The two way frequency table shows what a group of students did during the summer. Which statement is true related to the table?
Answer:
That statement is true which relates to what activity was taken by most of the students of different categories in that particular group during the summers.
Step-by-step explanation:
A two-way frequency table (likewise called a possibility table) is a valuable instrument for inspecting connections between downright factors. The passages in the cells of a two-way table can be frequency checks or relative frequencies (simply like a single direction table). Two-way frequency tables show what number of information focuses fit in every classification.
Assume you direct a review where you pose every individual two inquiries. When you have wrapped up the overview, you will have two bits of information from every individual. At whatever point you have two bits of information from every individual, you can arrange the information into a two-way frequency table.
A car traveling 9/10 of a mile per minute will travel _____ miles in 10 minutes
Answer:
It will travel 9 miles in 10 minutes
Step-by-step explanation:
A car travels 9/10 miles/minute
In 10 minutes, it will travel
10*9/10 = 9 miles
Final answer:
A car traveling at 9/10 of a mile per minute will travel 9 miles in 10 minutes by simply multiplying the car's speed by the time traveled.
Explanation:
To calculate how far a car traveling at a speed of 9/10 of a mile per minute will travel in 10 minutes, we simply multiply the speed of the car by the amount of time it travels.
Speed of car = 9/10 mile/minute
Time = 10 minutes
Distance traveled = Speed of car × Time
Distance traveled = (9/10) mile/minute × 10 minutes
Now we perform the multiplication:
Distance traveled = 9/10 × 10
Distance traveled = 9 miles
Simplify 3 x y x 2 x y x 4 x y
Answer:
24y
Step-by-step explanation:
y*y*y = y^3 (y to the power of 3)
3*2*4 = 24
then your left with 24 times y^3 which is 24y^3
Hope this helps!
The expression 3 x y x 2 x y x 4 x y when simplified is 24y³
How to simplify the expressionFrom the question, we have the following parameters that can be used in our computation:
3 x y x 2 x y x 4 x y
Evaluate the product of similar variables
So, we have
3 x y x 2 x y x 4 x y = 24 x y x y x y
Evaluate the remaining product of similar variables
So, we have
3 x y x 2 x y x 4 x y = 24y³
Hence, the product is 24y³
Read more about expression at
https://brainly.com/question/30492964
#SPJ6
determine the value of a so that when P(x)=a^2 x^3-3ax+1 is divided by x-2 there is no remainder
Calculate the number in the middle of -4 and 5
Answer:
0.5 is in the middle plz give branliest
Step-by-step explanation:
The distance between the numbers is 9
so if you divide them in half, you get 4.5
add 4.5 to -4 or subtract it from 5 to get 0.5
j/15=20 what does j equal?
Answer:
j=300
Step-by-step explanation:
You multiply each side by 15.
j=300
Answer:
j should equal 300.
Step-by-step explanation:
j/15=20
you have to get j by its self. what you do to one side you must do to the other.
j/15(15) = 20(15)
the fifteens cancel out
j=300
If anyone answers ALL i will give all my points and will give Brainliest
Answer:
too compelx illegal
Step-by-step explanation:
2c = 112
A. c = 2
B. c = 42
C. c = 56
D. C = 224
Answer:
The answer is C. 56
Step-by-step explanation:
So if we replace C with 56, the equation would look like this, 2(56)=112.
Which set of values makes the inequality n > -5 true?
{-5, -5.5, -6}
{-5, -4.5, -3)
{-6,0,5}
{-6, -7,-8}
Answer:
all false
Step-by-step explanation:
n > -5
{-5, -5.5, -6} False cannot = -5 ( all are greater than or equal to -5)
{-5, -4.5, -3) False cannot = -5
{-6,0,5} False cannot = -6
{-6, -7,-8}False these are less than -5
PLEASEEEEEE HELPPPP!!!!!!!!
A hospital cafeteria has 20 tables
65% of the tables have 6 chairs at each table
The remaining 35% of the tables have 4 chairs at each table
Complete the model
Then complete the statements to find the total number of chairs in the hospital
cafeteria
CLEAR
Number of tables with 6 chairs:
Number of tables with 4 chairs
20 total tables
65% of the tables have 6 chairs at each table. In total, there are
chairs at these tables
35% of the tables have 4 chairs at each table. In total, there are
chairs at these tables
Altogether, there is a total of
chairs in the hospital cafeteria.
Step-by-step explanation:
it means 13 tables have 6 chairs
and 7 tables have 4 chairs
so
total chairs in the cafeteria= 13×6 + 4×7 = 78+28=106
A combination lock uses 4 numbers, each of which can be 0 to 33. If there are no restrictions on the numbers, how many possible combinations are available?
Answer:
Solution for A combination lock uses 3 numbers, each of which can be 0 to 33. If there are no restrictions on the numbers, how many possible ...
Step-by-step explanation:
In the diagram below, what is the approximate length of the minor arc DE?
А. 6.3 cm
В. 3.1 cm
с. 5.2 cm
D. 7.9 cm
Answer:
6.3cm
Step-by-step explanation:
The approximate length of the minor arc DE will be 6.3 cm. Then the correct option is A.
What is a circle?It is a locus of a point drawn an equidistant from the center. The distance from the center to the circumference is called the radius of the circle.
Then the angle is subtended by the arc is 36° and the radius of the circle is 10 cm.
Then the length of the arc DE will be
[tex]\rm ARC = \dfrac{\theta }{360} \times 2\pi r[/tex]
Then we have
[tex]\rm ARC = \dfrac{36}{360} \times 2\pi \times 10\\\\ARC = 6.283 \approx 6.3\ cm[/tex]
More about the circle link is given below.
https://brainly.com/question/11833983
(giving 30 points/need answers STAT!!)
Four transformations of the function f(x) = 3x + 2 are given below.
For each transformation, drag the expression that shows the result of that transformation into the box under it.
Transformations can be applied to functions to change the appearance of
the (slope and intercept) of the function.
The result of the transformation are presented as follows;
[tex]\begin{tabular}{|c|c|c|c|}f(x-5)&f(x) - 5&-5 \cdot f(x) &f(-5\cdot x)\\3\cdot (x - 5) + 2&3 \cdot x - 5 + 2&-5\cdot (3 \cdot x + 2)&3 \cdot (-5\cdot x) + 2 \end{array}\right][/tex]Reasons:
The given function is; f(x) = 3·x + 2
The function -5·(3·x + 2) is the same as -5 × f(x) = -f(x)
Therefore;
-5·(3·x + 2) → -5·f(x)
The function 3·x - 5 + 2 = 3·x + 2 - 5 = f(x) - 5
Therefore;
3·x - 5 + 2 → f(x) - 5
The function 3·(x - 5) + 2 by comparison to 3·x + 2 is obtained when x is replaced by (x - 5), therefore;
f(x) = 3·x + 2
f(x - 5) = 3·(x - 5) + 2
3·(x - 5) + 2 → f(x - 5)
The function 3·(-5·x) + 2 is obtained when x in f(x) is replaced by (-5·x),
which gives;
f(x) = 3·x + 2
∴ f(-5·x) = 3·(-5·x) + 2
Which gives;
3·(-5·x) + 2 → f(-5·x)
The completed table is therefore;
[tex]\begin{tabular}{|c|c|c|c|}f(x-5)&f(x) - 5&-5 \cdot f(x) &f(-5\cdot x)\\3\cdot (x - 5) + 2&3 \cdot x - 5 + 2&-5\cdot (3 \cdot x + 2)&3 \cdot (-5\cdot x) + 2 \end{array}\right][/tex]
Learn more about transformation of functions here:
https://brainly.com/question/18076552
Two of the world's longest rivers are the Nile, which is 4100 miles long, and the Rio
Grande, which is 1900 miles long. Find how much longer the Nile is than the Rio
Grande.
Answer:
The Nile River is 2,200 miles longer than the Rio Grande.
Step-by-step explanation:
4100-1900=2200
Answer:
Answer:
The Nile River is 2,200 miles longer than the Rio Grande.
Step-by-step explanation:
4100-1900=2200
Step-by-step explanation: